Emprego de plantas com princípios tóxicos no controle de Meloidogyne enterolobii - Santos, Maria Lainara Lima dos (2015)
Root-knot nematodes (Meloidogyne spp) are among the most important plant pathogens, as they affect many crops, cause considerable losses to production and are difficult to control. The use of alternative methods, which do not leave residues that are harmful to the environment or to man, are the most advisable. This study was carried out both at the Laboratory of Phytopathology and in a greenhouse of the Plant Health Sector of the Department of Plant Science, in the Centre for Agrarian Science of the Federal University of Fortaleza. By means of four trials, it was sought to investigate the effect of toxic active ingredients present in nine plant species occurring in the State of Ceará, on M. enterolobii in vegetable crops. The species were pigeon pea (Cajanus cajan) 'Fava Larga', Crotalaria breviflora, pearl millet (Pennisetum glaucum) 'ADR 500', earpod tree (Enterolobium contortisiliquum), milkweed (Calotropis procera), jimson weed (Datura stramonium), metel (D. metel), neem (Azadirachta indica) and buckwheat (Fagopyrum esculentum). In the first trial, species susceptibility to the pathogen was investigated, where it was found that the C. breviflora, pearl millet, jimson weed, metel, neem and buckwheat behaved as if immune, whereas the pigeon pea, earpod tree and milkweed displayed different levels of resistance to the nematode. In the second trial, earlier cultivation of the nine species in an infested soil was evaluated for eradication of the pathogen by the later planting of lettuce (Lactuca sativa). The lettuce plants that followed the C. breviflora, pearl millet, jimson weed and neem did not present galls. However, the lettuce grown after the metel and buckwheat developed a few galls, and those following the pigeon pea, earpod tree and milkweed, showed a high number of galls. For the third test, incorporating the shoots of the pearl millet, the jimson weed, metel, buckwheat, earpod tree, milkweed and lettuce effectively reduced the population of nematodes in the soil, since no infestation was seen in the tomato plants grown after the procedure. In the fourth trial, the use of aqueous extracts of milkweed, earpod tree, jimson weed and metel in vitro resulted in 100% J2 mortality, demonstrating their strong nematicidal effect. Based on the results of the four trials it can be concluded that C. breviflora, pearl millet, jimson weed, metel and neem were effective in controlling M. enterolobii regardless of the way they were employed; this was probably due to the toxic ingredients present in their tissue, and shows them to be promising as an alternative form of control.